UPAYA PENINGKATAN MOTIVASI OLAHRAGA MELALUI PROGRAM “KOCIL” (KOMPETENSI CILIK DALAM PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA, DAN KESEHATAN DI MI MINHAJUTHULLAB TUNDAGAN - Abdulaziz, Muhammad; Febri Wijaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low student motivation for sports is a challenge in Physical Education, Sports, and Health (PJOK) instruction at MI Minhajuthullab Tundagan. This study aims to enhance students' sports motivation through the KOCIL (Little Competition) Program. The study employed the Kemmis and McTaggart Classroom Action Research (CAR) model, conducted over two cycles comprising planning, implementation, observation, and reflection stages. The research subjects consisted of 15 fourth-grade students. Data were collected through observation and analyzed using both quantitative and qualitative descriptive methods. The results indicate that the KOCIL Program successfully increased students' sports motivation. The percentage of students falling into the high and very high motivation categories rose from 20% in the pre-cycle stage to 60% in Cycle I and 93% in Cycle II. This improvement was evidenced by increased student participation, confidence, cooperation, discipline, and sportsmanship during lessons. Thus, the KOCIL Program proves effective as an innovative teaching strategy for boosting students' sports motivation in PJOK classes.